2014
DOI: 10.1007/s10995-014-1624-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age and Risk of Labor and Delivery Complications

Abstract: Objective We utilized an updated nationally representative database to examine associations between maternal age and prevalence of maternal morbidity during complications of labor and delivery. Study design We used hospital inpatient billing data from the 2009 United States Nationwide Inpatient Sample (NIS), part of the Healthcare Cost and Utilization Project (HCUP). To determine whether the likelihood that maternal morbidity during complications of labor and delivery differed among age groups, separate logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
168
3
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(229 citation statements)
references
References 60 publications
17
168
3
11
Order By: Relevance
“…Cavazos PA in their study, using age as an independent variable, concluded that the antenatal and labor delivery complications, low birth weight and preterm birth are higher in teenage and elderly gravida group. 9 Present study also depicted the same observation, as we had 23.9% preterm in elderly mothers and 27% in teenage group, higher than other reproductive age group. Females who sought antenatal care experienced less preterm rates (14.8%) as compared to the patients who never sought antenatal care (58.4%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cavazos PA in their study, using age as an independent variable, concluded that the antenatal and labor delivery complications, low birth weight and preterm birth are higher in teenage and elderly gravida group. 9 Present study also depicted the same observation, as we had 23.9% preterm in elderly mothers and 27% in teenage group, higher than other reproductive age group. Females who sought antenatal care experienced less preterm rates (14.8%) as compared to the patients who never sought antenatal care (58.4%).…”
Section: Discussionsupporting
confidence: 89%
“…Singh Uet al reported a neonatal mortality rate of 12.7% and Das A reported an incidence of 20.48%. 13,9 The rates of neonatal death remain high irrespective of the type of intensive care facilities. Prolonged hospital stays and NICU admission add to the cost and impose a burden on existing health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that early marriage before 20 years is common in many parts of our country. This is in contrast to the studies conducted by Cavazos Rehg et al 13 .Similarly the association of increased BMI with increased incidence of preeclampsia is shown in various studies. In this study we found that women with a BMI more than 30 were more likely to develop preeclampsia than those with BMI less than 30.…”
Section: Discussioncontrasting
confidence: 73%
“…Usia yang terlalu tua berkaitan dengan kemunduran dan penurunan daya tahan tubuh serta berbagai penyakit yang sering menimpa seperti hipertensi, diabetes, solusio plasenta, prematur, lahir mati, partumbuhan janin yang buruk dan plasenta previa. Semakin muda atau semakin tua usia ibu saat hamil akan semakin berisiko untuk ibu mengalami komplikasi saat hamil dan melahirkan (Cavazos et al, 2015).…”
Section: Hasilunclassified